Aldose to ketose interconversion: galactose and arabinose isomerization over heterogeneous catalysts. Issue 22 (31st May 2017) - Murzin, Dmitry Yu.; Murzina, Elena V.; Aho, Atte; Kazakova, Mariya A.; Selyutin, Alexander G.; Kubicka, David; Kuznetsov, Vladimir L.; Simakova, Irina L.
Abstract : Isomerization of glucose, galactose and arabinose to corresponding keto-sugars was studied in the present work over a range of heterogeneous catalysts. Abstract : Isomerization of glucose, galactose and arabinose to corresponding keto-sugars was studied in the present work over a range of heterogeneous catalysts. Magnesium aluminates with different ratios between oxides resulting in materials with a Mg/Al ratio from 0.2 to 0.9 were prepared, characterized and evaluated in terms of their catalytic behavior. The catalyst with a Mg/Al ratio close to hydrotalcites was the most efficient considering activity, selectivity and stability. The sugar structure was shown to have a minor influence on catalytic activity and selectivity.